Experimenting and modelling the role of road surface detritus in the formation of potholes - Djabatey, Charles (2023)
Although potholes are a perennial problem in UK roads, the mechanisms of their formation are poorly understood. There is no established experimental method to characterise the pothole resistance of an asphalt mixture or means of specification directly related to this phenomenon. Inspired by recent progress in geophysics, this research models the potential mechanisms of crack propagation in asphalt, under the conditions considered to increase the likelihood of this form of deterioration and develops a novel experimental framework to validate these models.